Proton pump inhibitors vs. histamine receptor 2 antagonists in gastric protection in the anticoagulated patient: what has the evidence defined? - Duarte-Duran , Angie S. (2024)
Objective: to evaluate the latest evidence on the difference in gastroprotection generated by proton pump inhibitors (PPIs) and histamine receptor 2 antagonists (H2RAs) in anticoagulated patients, as well as the associated risk of gastrointestinal bleeding. Methods: narrative review. A literature search was conducted in the PubMed, ScienceDirect, Web of Science, and MEDLINE databases. Results: Among the described mechanisms explaining bleeding in the gastrointestinal tract are mucosal damage, alterations in local pH, platelet inhibition, coagulation factor alteration, and vascular lesions. Depending on the pharmacological group, anticoagulants can act on different targets in the coagulation pathway, altering the factors involved in this pathway and potentially triggering bleeding. Antisecretory drugs, on the other hand, aim to inhibit or reduce gastric acid secretion through interaction with enzymatic systems, altering the local pH. Thus, these drugs influence the risk of bleeding. However, the latest evidence shows that PPIs reduce the likelihood of gastrointestinal bleeding by up to 33% compared to H2RAs, without impacting other outcomes such as mortality or hospitalization. Conclusion: Although the evidence is scarce and heterogeneous, it was observed that there is greater scientific support and gastroprotective benefit against the frequency of gastrointestinal bleeding with the use of PPIs compared to H2RAs in anticoagulated patients who concurrently use gastric acid suppressants.